Characterization of pili protein with molecular mass of 85 kDa Escherichia coli as an adhesin and a hemagglutinin - Dini Agustina; Siti Marissa Aisyah; Ika Rahmawati Sutejo; Diana Chusna Mufida (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Escherichia coli (E. coli) is a rod-shaped gram-negative bacterium included in Multi Drug Resistant (MDR) bacteria. There are several strategies in place to prevent and treat E. coli bacterial infections to reduce some the incidences of MDR. One of them is the development of a protein-based vaccine. Pili is one of virulence factors in E. coli surface proteins that can mediate attachments of bacteria to host cells (adhesin or hemagglutinin) and can be used as protein-based vaccine candidates. Objective: This study aims to determine characterization of pili protein with molecular mass of 85 kDa Escherichia coli bacteria as an adhesin and a hemagglutinin. Methods: This study is a true experimental laboratories and a descriptive study to determine roles of pili protein with molecular mass of 85 kDa as an adhesin and a hemagglutinin. Samples used in this study were a stock of E. coli in the Microbiology Laboratory Faculty of Medicine, Universitas Negeri Jember (UNEJ). A hemagglutination test in this study used mouse erythrocytes while an adhesion test used mouse enterocytes. Isolation and purification of E. coli pili protein, isolation of mouse erythrocytes, isolation of mouse enterocytes, the hemagglutination test and the adhesion test were methods in this study. A data analysis with a correlation-regression was used to determine relationships between the adhesion index and titer pili 85 kDa with a limit of significance, 0.05 (p <0.05). Results: The hemagglutination test showed no ability of agglutination with the formation of red aggregate points starting from the first dilution. An analysis with Pearson correlation indicated a relationship between titer pili 85 kDa E. coli and adhesion index (p = 0.009; R = -0.921).Conclusion: Pili protein 85 kDa E. coli plays a role as an adhesin protein and do not have a role as a hemagglutinin protein.